Peranan Abbot Sebagai Representasi Kristus dan Implikasinya dalam Pendidikan Anak Usia Dini - Meiliana Evita Benes (Indonesian Journal of Theology, 2021)
The presence of the spiritual leaders who have the absolute power is aptly directly related to the spiritual growth of the people whom they served. Abbots in monastic times are examples of leaders with high qualifications to perform instructional tasks related to spiritual formation. The development in history shows the change and complexity of this role. Abbots’ role is important not only for the adults, but also for the children—even to the early childhood. Because spiritual leaders are present as representatives of Christ to show true, authentic, whole, and balanced love. Christ is the primary authority in this instructional process. Early childhood also needs the presence of authorities to support their spiritual formation. To achieve this goal, it is important to consider the role of spiritual leaders and spiritual needs based on early childhood development.